ENVIRONMENTAL EDUCATION, STUDENT PROTAGONISM AND COOPERATION: A PROPOSAL FOR CREATING AN ECO-SCHOOL - Kologeski, Anelise; da Costa, Luciano Andreatta Carvalho; Robaina, Jose Vicente Lima (Seven Editora, 2025)
This article discusses environmental education from a critical perspective, linked to student protagonism and cooperation, and proposes the creation of an eco-school as a pedagogical and political strategy for Brazilian basic education. Based on theoretical references in environmental education, whole-child education, cooperativism and education for sustainable development, it analyzes the potential of school as a space for the formation of ecological, critical and supportive subjects, capable of ethically and responsibly intervening in the socio-environmental reality. The article advocates the importance of interdisciplinary and participatory projects, implemented through science clubs and cooperative practices, articulated with the principles of the Eco-Schools Programme, as pathways to build a culture of sustainability in everyday school life. Finally, it presents the expected results and the possible formative, institutional and community impacts of implementing an eco-school, with emphasis on the development of autonomy, student authorship and environmental citizenship.DOI: https://doi.org/10.56238/sevened2025.038-060